Determinación de la presencia de Salmonella spp en carne de pollo comercializado en ferias libres del cantón Loja - Robles Jumbo, Darwin Alexandro (2017)
This research work was developed with the purpose of determining the presence of Salmonella spp in chicken meat sell in farmer´s –markets of four urban parishes in Loja Canton. For this purpose, 72 samples of meat with an average weight of 250 g. were analyzed using microbiological system "3M Petrifilm Salmonella express". A simple random sampling was applied. The variables in the study were the presence of Salmonella spp, sanitary conditions of home slaughtering (by survey), physical analysis of meat (color, odor, appearance and pH) biochemical and genotyping tests. The statistical program Sas University Edition 2016 package EpiR was used to determine prevalence and 95% confidence intervals. The prevalence of Salmonella spp was 0% and confidence interval (CI of 0) - 4.95% in the 72 samples, as well as prevalence of 0% and 0 CI - 17.8% in 18 samples of each market (La Tebaida, San Sebastián, Mayorista and Las Pitas). The applied sanitary conditions of home slaughtering are deficient in the process. The physical analysis in the meat was obtained with a color average (scale 1-5) from 2.67 (deep pink); 97.22% of channels with pleasant smell (sui-generis); 93,06% normal appearance and average pH of 5.98. In conclusion, the presence of Salmonella spp. was not evidenced in the samples analyzed, as well as, the meat that is sold in the farmer´s-markets do not have problems in terms of the physical characteristics mentioned above.